Explaining user satisfaction with academic libraries: strategic implications - Andaleeb, Syed Saad; Simmonds, Patience L. (© American Library Association, Chicago, 2016)
This is an Open Access Article. It is published by College & Research Libraries (C&RL) is the official scholarly research journal and the definite version is available at: http://doi.org/10.5860/crl.59.2.156 The Journal's Retrieved from http://crl.acrl.org/content/59/2/156